2015
DOI: 10.1007/s13277-015-4673-7
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DP is the cervical cancer susceptibility loci among women infected by high-risk human papillomavirus: potential implication for triage of human papillomavirus-positive women

Abstract: Given that only a small proportion of women infected by high-risk human papillomavirus (hrHPV) develop cervical cancer, it's important to identify biomarkers for distinguishing women with hrHPV positivity who might develop cervical cancer from the transient infections. In this study, we hypothesized that human leukocyte antigens (HLA) susceptibility alleles might contribute to cervical cancer risk among females infected by hrHPV, and interact with hrHPV types. A case-control study with 593 cervical cancer case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…For those participants with normal cytology, a colposcopy was not routinely used unless they were HPV16 or 18-DNA positive. High-risk HPV prevalence was 97.7% (593/607) in cervical cancer patients and 8.0% (407/5066) in cancer-free individuals [25]. In the current study, all HPV16/18positive controls accepted colposcopy and showed negative results.…”
Section: Study Participantsmentioning
confidence: 41%
“…For those participants with normal cytology, a colposcopy was not routinely used unless they were HPV16 or 18-DNA positive. High-risk HPV prevalence was 97.7% (593/607) in cervical cancer patients and 8.0% (407/5066) in cancer-free individuals [25]. In the current study, all HPV16/18positive controls accepted colposcopy and showed negative results.…”
Section: Study Participantsmentioning
confidence: 41%
“…Interestingly, only a few months later, another study conducted with Norwegian patients also report similar susceptible loci DQA1 and DQB1 in the MHC region, with partial but not complete overlap . From then on, many more variants of MHC genes were discovered and confirmed to be correlated with cervical cancer in various populations . Wu et al.…”
Section: Key Factors That Contribute To Hpv Persistence and Cervical mentioning
confidence: 99%
“…Jia et al. . found three HLA‐DP SNPs (rs4282438, rs3117027, and rs3077) to be significantly associated with the risk of cervical cancer.…”
Section: Key Factors That Contribute To Hpv Persistence and Cervical mentioning
confidence: 99%
See 1 more Smart Citation
“…The HLA-DP genetic variants have been recognized to correlate with occult hepatitis B infection (Mardian et al, 2017), and it has been shown that HLA-DQ polymorphisms as protective factors are connected to HBV-related hepatocellular carcinoma (Gao et al, 2016). Additionally, HLA-DP and HLA-DQ variants are involved in the progression of other diseases, such as graft-versus-host disease and cervical cancer (Jia et al, 2016;Morishima et al, 2018). HLA genes encode molecules that are central to the host immune response, and variation in these genes likely predicts the outcome of infectious diseases (Crux & Elahi, 2017).…”
Section: Introductionmentioning
confidence: 99%